Long-term health of children conceived after assisted reproductive technology - Christina Bergh; Ulla-Britt Wennerholm (Upsala Journal of Medical Sciences, 2020)
The aim of this narrative review is to summarize the present knowledge on long-term outcome of children born after assisted reproductive technologies (ART). The main outcomes covered are neurodevelopment including cerebral palsy, cognitive development, attention deficit hyperactivity disorder and autism spectrum disease, growth, cardiovascular function, diabetes type 1, asthma, malignancies, and reproductive health. Results have mainly been obtained from systematic reviews/meta-analyses and large registry studies. It has been shown that children born after ART, when restricted to singletons, have a similar outcome for many health conditions as their spontaneously conceived peers. For some outcomes, particularly cardiovascular function and diabetes, studies show some higher risk for ART singletons or subgroup of ART singletons. The fast introduction of new ART techniques emphasizes the importance of continuous surveillance of children born after ART.